4 Of Earth and Stone: The Materiality of Maya Farmers' Everyday Lives at Chan, Belize. Issue 1 (September 2015) - Robin, Cynthia; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT This chapter explores the materials and materiality of the everyday lives of farmers living in the ancient Maya farming community of Chan located in west central Belize. Limestone bedrock and soil matrix were the substance of Chan's landscape. In constructing their community and across their daily lives, Chan's residents used, modified, and transformed earth and stone to build houses, agricultural terraces, quarries, and workshops that were the basis of everyday life at Chan. The local resources and products that residents created from earth and stone were critical in their development of a resilient community. Exploring the materiality of the everyday lives of Maya farmers provides a fertile ground for understanding the significance of ordinary people's daily lives in the past.